Manis Bakery Sdn. Bhd. / Nur Syahirah Rusli … [et al.] - Rusli, Nur Syahirah; Hashim, Nur A’lin Syahmina; Mohd Sukri, Nur Aina Syahirah; Dzulkili, Siti Zuliana; Syamsul Bahri, Nur Shafidatul Elisa (2021)
Business plan is a written document which is the opportunity for entrepreneur to assess the business venture objectively, critically and practically. Besides, it is also as a guideline for day-to-day management of the business. Business plan is very important before starting a business to make sure the business can run smoothly and effectively. Manis Bakery Sdn. Bhd. offers the best desserts that are produce with love to our customer and we only provide the high quality, delicious and fresh dessert which can give satisfaction to the customer. This business is based on partnership with four leaders holding important position in the organization along with Miss Nurshafidatul Elisa Binti Shamsul Bahri as the General Manager, Miss Siti Zuliana Binti Dzulkifli as the Administrative Manager, Miss Aina Syahirah Binti Mohd Sukri as the Operational Manager, Miss Nur Syahirah Binti Rusli as the Marketing Manager and Miss Nur’Alin Syahmina Binti Hashim as the Financial Manager. The main objective of this company are to provide only high quality desserts with reasonable price to ensure our customers are satisfied with our desserts. This is because there are too many high quality desserts out there that are sold at high prices, so, we plan to open a bakery that sells high quality desserts in terms of the taste and the texture at a reasonable price. We want to give the best to our customer so that we are able to gain their trust and loyalty. One of our target market is families from middle income consumer and young generation that have interest to buy our desserts. We have chosen to open our business at Petaling Jaya due to the demand for delicious desserts and sold at a reasonable price is very high there. The location of the business is also strategic because near to the residential area, Sixth Form College, KTM Setia Jaya and other necessary shop such as grocery shop and stationary shop.